First Report of Septoria centellae Associated with Leaf Spot of Centella asiatica in Korea - Park, Ji Hyun (2011)
Septoria centellae associated with leaf spot of Centella asiatica is reported for the first time in Korea. The fungus is described and illustrated in detail. It is also compared with related species of Septoria present on Centella and Hydrocotyle spp. with taxonomic comments. Two monoconidial isolates from Jeju and Wando were successfully cultured and have been deposited in the Korean Agricultural Culture Collection.